The residue of salinomycin in the muscles of olive flounder (Paralichthys olivaceus) and black rockfish (Sebastes Schlegeli) after oral administration analyzed by LC-Tandem-MS - Seungjin Lee; Won-Sik Woo; Jaekyeong Kim; Yeongwoon Jin; Jin Woo Lee; Jung-Soo Seo; Mun-Gyeong Kwon; Ji-Hoon Lee; Chan-Il Park; Sang Hee Shim (BMC Veterinary Research, 2024)
Abstract Background Salinomycin, an antibiotic, have potential as a veterinary drug for fish due to its anti-parasitic activity against several fish parasites. Thus the residual levels of salinomycin in muscles of two significant aquaculture species in Korea, olive flounder and black rockfish, were analyzed using HPLC-MS-MS. Results The proper method to analyze the residual salinomycin in fish muscles using LC-MS-MS was settled and the method was validated according to CODEX guidelines. The residues in three distinct groups for two fish species were analyzed using the matrix match calibration curves at points of five different times following oral administration. After oral administration, salinomycin rapidly breaks down in both olive flounder and black rockfish. After 7th days, the average residue in all groups of two fish spp. decreased below limit of quantitation (LOQ). Conclusion Due to low residue levels in fish muscles, salinomycin may therefore be a treatment that is safe for both fish and humans. This result could contribute to establishment of MRL (minimal residual limit) for approval of salinomycin for use in aquaculture.